Perception of Teachers on Principals' Leadership Styles on Students' Discipline in Public Secondary Schools in Ugunja Sub-County, Kenya - Odongo, Yambo W. (JOOUST, 2015)
Leadership style is the single most important factor in the success or failure of a school's discipline endeavours. The Principal has a responsibility to instill the same. Despite this robust role entrusted with the principals, learning institutions in Kenya especially public secondary schools have been plagued with different cases of unrest emanating from students, teachers and other staff members. The purpose of this study was to find out the perceptions of teachers on principals' leadership styles on students' discipline in public secondary schools in Ugunja sub-county, Kenya. The research objectives were; to find out the leadership styles adopted by principals in public secondary schools in Ugunja sub - county, to examine the extent at which principal's leadership styles influence discipline in public secondary schools in Ugunja Sub-County, to find out how the principals' leadership styles determine the strategies used in instilling students' discipline. The study was based on social learning theory and transformational theory. A descriptive research design was used. The units of analysis were 22 public Secondary Schools, 22 Principals, 218 teachers, and 3000 form three students. The sample consisted of 22 Principals, 218 teachers and 300 students. Saturated sampling was used to select 218 teachers and the 22 Principals while a systematic sampling technique was used to select the 300 students for the study. Data was collected using the questionnaire and interview schedules. Quantitative data was analyzed through the use of descriptive statistics which included frequencies, percentages and means as measures of central tendency, while the qualitative data was analyzed through the use of content analysis. The analyzed data was presented using tables and bar charts. The findings of this study reveal that Principals of secondary schools in Ugunja Sub-county do employ various leadership styles especially autocratic, democratic and transformational styles. The study also establishes that schools were using hierarchical leadership style to some extent and that all teachers were not ready for the style of leadership. The style employed in schools do fuel animosity among the students as such, continue fueling indiscipline in schools. Based on the findings, the study concludes that autocratic leadership was the most preferred style in management of discipline in secondary schools. The study also concludes that leadership style used by principals heavily affect discipline in secondary school. The study also concludes that autocratic leadership does make the learners to be more indiscipline than democratic leadership style. Based on the study conclusion, the study recommended that all principals should undergo leadership training to understand the relevancy of styles in discipline management. The study also recommends that most Principals should evaluate their styles of leadership on a yearly basis to help in modifying their styles to the best discipline management. From the conclusion, the study recommended that there should be regular consultation between the principals and quality assurances offices on discipline management. Lastly the study recommended that Principals should ensure that they have regular meetings with the student council on discipline matters so as to help in knowing the best approach to use. A study should be done on the influence of school factors on student discipline in secondary schools.
Keywords: Perception of Teachers.; Leadership Styles on Students.; Discipline in Public Secondary Schools.; Kenya.